PERBANDINGAN EFEKTIVITAS MODEL PEMBELAJARAN TIPE NUMBERED HEADS TOGETHER DAN TEAM ASSISTED INDIVIDUALIZATION PADA MATERI STATISTIKA SISWA SMP NEGERI 1 REMBOKEN - Pangemanan, Aaltje; Wenas, John Roby; Slamet, Marlisa (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. This research was aimed to determine the differences of the student learning outcomes on those who used the NHT model of learning, TAI model and DI model on statistic lessons. This research was conducted at SMP Negeri 1 Remboken during the odd semester of the 2019/2020 academic year. Data analysis employed the Anova statistic found that the average learning outcomes of the first experimental group, whom treated using the NHT model of learning, were the highest among the compared groups, which scored 82.2. The average of the students learning outcomes of the second experimental group, who used the TAI model was 70.32 and the average of the students learning outcomes of the control class who used the Direct Instruction model was 66.72. Based on the ANOVA results, it was concluded: (1) The average of the students learning outcomes who used the NHT model were more the average of the students learning outcomes who used the TAI model, (2) The average of the students learning outcomes who used the NHT model was more the average of the students learning outcomes who used the DI model, (3) The average of the students learning outcomes who used the TAI model was more the average of the students learning outcomes who used the DI model.Â Key Words: DI, NHT, TAI, The Students Learning Outcomes